Embrionary and larval development of the marine clam Tivela mactroides (Bivalvia:Veneridae)in Zulia State,Venezuela - Yinett M Reverol; José G Delgado; Yajaira G de Severeyn; Héctor J Severeyn (Revista de Biología Tropical, 2004)
The marine clam,Tivela mactroides ,from Caño Sagua beach,Venezuela,was spawned and reared under laboratory conditions to monitor its early development.Spawning was spontaneous but in some cases it had to be induced by the additon of eggs and sperm.After fertilization,the embryonic development occurred at 5 hr approximately. Trochophore larvae were observed between eight and ten hours later.Straight-hinged veliger stage appeared 15 hr after fertilization.Transition from veliger stage to the umbo stage occurred about eight days after fertilization.Pediveliger stage was observed 22 days after fertilization.Metamorphosis of T.mactroides was not successful under our laboratory conditions;probably the bacterial contamination and subsequent mortalities were important factors constraining the final phase of the larval cycle.However,in a few cases young individuals were observed.We suspect that this was due to unfavorable conditions (e.g.:bacterial contamination, unsuitable food availability,etc.)and the broad variation in developmental times,suggesting that these stages might be particularly sensitive to environmental changes.These results may not necessarily reflect what happens under natural conditions.Rev.Biol.Trop.52(4):903-909.Epub 2005 Jun 24. La almeja Tivela mactroides ,de la playa Caño Sagua, Venezuela,fue desovada y cultivada bajo condiciones de laboratorio,monitoreando su desarrollo embrionario y larvario.El desove fue espontáneo,sin embargo,en algunos casos se indujo adicionando óvulos y espermatozoides. El desarrollo embrionario se produjo en cinco horas, aproximadamente.La larva trocófora fue observada a las diez horas,mientras que la prodisoconcha aparece a las 15 horas después de la fertilización.La larva disoconcha aparece ocho días después de la fecundación y la veliconcha,aproximadamente a los 20 días.La metamorfosis de T.mactroides no fue satisfactoria bajo estas condiciones, ya que la contaminación bacterial fue uno de los principales factores que provocó la mortalidad de las larvas durante la fase final del ciclo,sin embargo,en algunos casos, se observaron juveniles.Las condiciones no favorables (contaminación bacteriana,disponibilidad de alimentos, etc.)y la variación en los tiempos de desarrollo,sugieren que estos estadios son muy sensibles a los cambios ambientales. Estos resultados no necesariamente reflejan lo que ocurre en el medio natural.